Nonstandard do-not-resuscitate orders. Issue 2 (April 2019) - Holt, Gregory E.; Goodman, Kenneth W.; Olvey, Stephen E.; Kett, Daniel
Abstract : Purpose of review: Tattoos and medallions are examples of nonstandard do-not-resuscitate (DNR) orders that some people use to convey end-of-life wishes. These DNR orders are neither universally accepted nor understood for reasons discussed within this manuscript. Recent findings: Studies show both providers and patients confuse the meaning and implication of DNR orders. In the United States, out-of-hospital DNR orders are legislated at the state level. Most states standardized out-of-hospital DNR orders so caregivers can immediately recognize and accept the order and act on its behalf. These out-of-hospital orders are complicated by the need to be printed on paper that does not always accompany the individual. Oregon created an online system whereby individuals recorded their end-of-life wishes that medical personnel can access with an Internet connection. This system improved communication of end-of-life wishes in patients who selected comfort care only. Summary: To improve conveyance of an individual's wishes for end-of-life care, the authors discuss nationwide adoption of Oregon's online registry where a person's account could comprehensively document end-of-life wishes, be universally available in all healthcare institutions, and be searchable by common patient identifiers. Facial recognition software could identify unconscious patients who present without identification.